AGE, GENDER, EDUCATIONAL LEVEL, OCCUPATIONAL, AND KNOWLEDGE LEVEL ABOUT MULTIDRUG RESISTANT TUBERCULOSIS (MDR-TB) AMONG TUBERCULOSIS PATIENTS - Rozi, Fahrur; Fiddaroini, Fakhrun Nisa’; Prawito, Prawito (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Resistance of Mycobacterium Tuberculosis is a condition in which Anti-Tuberculosis (OAT) drugs are unable to kill the Mycobacterium Tuberculosis germs. One type of resistance is Multidrug Resistant Tuberculosis. Multidrug Resistant Tuberculosis (MDR-TB) is TB caused by TB bacteria that are resistant to 2 types of OAT, namely INH and Rifampin. The consequences if resistance to OAT are deterioration of health, increased costs, prolonged treatment, high rates of therapy failure and death. Objective: This study aimed to determine relationship between age, gender, educational level, occupational, and knowledge level about multidrug resistant tuberculosis (MDR-TB) among tuberculosis patients at the Kanigaran Public Health Center, Probolinggo City. Methods: This study used a cross sectional research design with a sample of 60 respondents with pulmonary TB undergoing treatment at the Kanigaran Public Health Center, Probolinggo City. Data was collected using a questionnaire with an ordinal scale which was then analyzed using the Spearman Rank statistical test. Result: Based on the research results, it was found that only age and educational level had a relationship with knowledge level (r = -.291, p = .024; r = .470, p = .000; respectively). Conclusion: The level of knowledge of TB patients about multidrug-resistant TB (MDR-TB) can be influenced by education level and age, so that health workers can provide an understanding related to MDR-TB according to the level of education and age of the TB patient.